Home with you - McCoy, Shirlee (McCoy, Shirlee. Bradshaw brothers., 2018)
Sullivan Bradshaw is in way over his head. A car crash killed his brother, Matthias, and critically injured his sister-in-law. It<U+2019>s Sullivan's turn to care for the couple<U+2019>s six children and the ancestral farm, but the die-hard bachelor and art professor is hardly family-man material. What he needs is the perfect nanny-miracle worker-saint. What he gets is pretty Rumer Truehart, a free spirit who will change everything he ever thought he wanted . . . Rumer learned the hard way that nothing is for sure, much less forever. And she certainly understands why Sullivan<U+2019>s unhappy childhood makes him a strictly no-commitments kind of guy. But she can't help being drawn to this thoughtful, gentle man. And when trouble strikes, she<U+2019>s determined to win his trust<U+2014>and show him love can be a promise for keeps.